Optimalisasi Wakaf dalam Kajian Kitab Fathul Qorib pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Optimizing Waqf in the Study of the Book of Fathul Qorib in Book Subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Vidia Novianti; Puji Lestari; Fatimah Nurani Normarista; Amelinda Putri Pangesti (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
This study aims to explore the role of teaching the Fathul Qorib book in instilling the values of waqf optimization at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta. The method applied in this study is qualitative with a descriptive approach. The findings show that the boarding school not only transfers theoretical knowledge of waqf fiqh, but also successfully encourages the internalization of values through a contextual approach. The educational process links classical concepts in Fathul Qorib, such as habs al-ashl wa tasbil al-tsamarah (retaining the principal and distributing the proceeds), with modern ideas such as productive waqf and social investment. The process of internalizing values takes place through three stages: cognitive, affective, and psychomotor, which prepare students not only with a deep understanding of the law but also with vision, creativity, and managerial skills to become skilled nazhir (waqf managers). Thus, Islamic boarding schools play a role in producing prospective nazhir who are able to optimize waqf as a sustainable economic tool, without deviating from the basic principles of fiqh.